TOURIST ASPIRATIONS ON SANKARANARAYANAR TEMPLE AT SANKARANKOVIL, TENKASI DISTRICT – A STUDY (International Journal of Food and Nutritional Sciences, 2022)
Tourist aspirations refer to the inherent desire, instinct, needs, and preferences that drive individuals to visit or travel to specific destinations. Sankaranarayanar Temple, a renowned Hindu religious site, attracts both domestic and international tourists, irrespective of their religious or non-religious affiliations. This research paper aims to investigate the factors that inspire tourists to visit Sankaranarayanar Temple. The primary objective of this study is to identify the key motivators that prompt individuals to choose Sankaranarayanar Temple as their destination. A total of 196 participants were selected as the sample respondents for this study. Statistical tools such as percentage analysis and mean were employed to analyze the collected data. The findings indicate that a significant majority of the respondents visit the temple to fulfill their religious obligations and seek solace and tranquility.